A new built-in loopback test method for Digital-to-Analog Converter frequency response characterization. (September 2021) - De Vito, Luca; Picariello, Francesco; Rapuano, Sergio; Tudosa, Ioan
Abstract: The paper presents a novel loopback test method for frequency response characterization of Digital-to-Analog Converters (DACs). As in traditional loopback test method, the DAC output is acquired by means of a digitizer. However, by relying on Compressive Sampling (CS), the proposed method reduces the sampling frequency requirements for the digitizer allowing to embed it in the DAC. In this case, an automatic compensation of the DAC frequency response can be implemented. In the paper, the mathematical formulation of the method and its experimental evaluation are presented. The obtained results demonstrate that the proposed measurement method based on CS could benefit from a significant sampling rate reduction respect to the Nyquist one.